Invalid Contract - Morales Hervias, Rómulo (2005)
This paper examines the invalidity of contracts within the framework of the theory of legal transactions, focusing on nullity and voidability. This analysis shows that the invalidity of contracts, and in particular the distinction between nullity and voidability, is a complex task that requires a deep understanding of the nature of the legal transaction. It is therefore argued that it is necessary to go beyond the category of legal act in order to understand and explain the theory of invalidity and its application in practice. In this context, the author addresses three important points in order to delimit the distinction between the two main types of contractual invalidity: the organic conception of invalidity, the social conception of invalidity and the normative conception of invalidity. By understanding each of these conceptions, the author concludes by pointing out the scope of protection that corresponds to both nullity and voidability.